Pharmacology of Airway Goblet Cell Mucin Release - Kwang Chul Kim; Akinori Hisatsune; Do Jin Kim; Takeshi Miyata (Elsevier, 2003)
Airway mucus hypersecretion is one of the major clinical manifestations of patients suffering from various pulmonary diseases. However, no drugs are yet available to control airway mucus hypersecretion. For the past 15 years, a plethora of information has amassed with regard to the pharmacology of airway goblet cell mucin secretion using various primary cell culture systems. The recent discovery of various MUC genes has also greatly stimulated research in this field. Nevertheless, the heterogeneity of the oligosaccharide structure of mucin molecules makes it extremely difficult to assess the significance of the information derived from the pharmacological studies. Therefore, it seems crucially important to understand the roles of individual mucins in conjunction with normal airway physiology and pathology, which should be the future research directions necessary for studying airway goblet cell mucin pharmacology.